INFLUENCE BOARD OF DIRECTORS AND AUDIT COMMITTEE ON PERFORMANCE FINANCE COMPANY - Fachrudin Fachrudin; Charvin Charvin (SEAN Institute, 2023)
This research aims to analyze the magnitude of the influence of several characteristics of the size of the board of directors, the frequency of board commissioner meetings, and the competence of the audit committee on financial performance in construction companies in 2018–2022, with company age as a moderating variable. The theory of this research refers to agency theory and good corporate governance. This research is empirical, using data from audited financial reports on construction companies published in the period 2018–2022. Data analysis uses panel data regression analysis. Based on the results of panel data regression analysis with a significance level of 78% using the Eviews 12 application, This research uses ROE and Tobin's Q measurements to test the company's financial performance. The research results show that the size of the board of directors does not have a significant positive effect on financial performance based on ROE and Tobin's Q. Based on ROE, the frequency of board of commissioners meetings has a significant negative effect on financial performance, while based on Tobin's Q, the frequency of board of commissioners meetings has a significant positive effect on financial performance. Based on ROE and Tobin's Q, audit committee qualifications do not have a significant effect on financial performance. This research also shows that the size of the board of directors, the frequency of board of commissioners meetings, audit committee qualifications, and company age together or simultaneously influence financial performance.